Hydrothermal Synthesis of Zn₂SnO₄ Nanoparticles for Ethanol Sensor - Lai, Van Duy; Nguyen, Hong Hanh; Nguyen, Duc Hoa; Chu, Manh Hung (Old Journal, 2019)
Zn₂SnO₄ nanoparticles were synthesized by a facile hydrothermal method for a C₂H₅OH gas-sensing application. The synthesized materials were characterized by field-emission scanning electron microscopy, powder x-ray diffraction and Raman spectroscopy. Gas sensing characteristics were measured at various concentrations of C₂H₅OH in temperature ranging from 350 to 450°C. Results pointed out that the sensor showed the highest response values at operating temperature of 450°C. The sensor response increased linearly with ethanol concentrations in the range of 125–1500 ppm. The results indicated that the hydrothermally synthesized Zn₂SnO₄ nanoparticles might be a promising candidate material for C₂H₅OH gas sensor.